The Development of Educational Human Resources through Indonesia’s Education System - Ningsih, Ayu Rahma; Mentari, Sri; Julyanto, Rio; Safrudin, Safrudin (International Journal Labs, 2022)
Background: Human resources (HR) is one of the important factors in development. Macro-terms, development input factors, such as natural, material and financial resources will not provide optimal benefits for the improvement of people's welfare if not supported by adequate availability of HR factors, both in quality and quantity. Aim: This research aims to develop human resources, in essence directed in order to improve quality which in turn will be able to increase productivity. Method: This study was carried out through the method of collecting secondary literature data, and the results of relevan previous studies, data and information sourced from secondary data and studies which are then analyzed using a conceptual approach, human resource management. Findings: Human resource development can be done through training, education, performance assessment, and career development. The model of the development of educational human resources in the context of the national education system should refer to the achievement of standards of educators and education personnel.